Hubungan Tingkat Pengetahuan Masyarakat tentang Tanaman Obat Keluarga (TOGA) dengan Penerapannya sebagai Pengobatan Tradisional di Kecamatan Dawe Kabupaten Kudus - Naim Matul Khoiriyah; Ria Etikasari; Galih Kurniawan (Universitas Muhammadiyah Klaten, 2026)
Family Medicinal Plants (TOGA) are plants cultivated in home gardens and traditionally utilized as natural, safe, and affordable treatments. Indonesia has approximately 15,000 species of medicinal plants, but only about 7,000 are actively utilized. This study aims to analyze the relationship between the level of community knowledge and the application of TOGA as traditional medicine in Dawe District, Kudus Regency. This study employed a cross-sectional observational design. The study subjects consisted of 391 randomly selected respondents from Puyoh and Cendono villages. Data were collected through questionnaires and analyzed using descriptive statistics and the Chi-Square test. The results showed that 58.3% of respondents had good knowledge of TOGA, and 55% applied it as traditional medicine. The Chi-Square test revealed a significant relationship between knowledge level and TOGA application (p < 0.05). Respondents with higher levels of knowledge tended to apply TOGA more optimally.